East meets west: integrating Yin-Yang theory with immunology teaching - Wang, Zhiyong; Wang, Min; Lin, Mao; Lu, Yanxin; Xia, Qiang; Wei, Pei (Frontiers in Immunology, 2024)
This perspective article delves into a novel integration of Yin-Yang theory-an ancient Chinese philosophical cornerstone-with the sophisticated realm of immunology. Given the intricate concepts inherent in immunology, many students find it challenging to comprehend the delicate mechanisms governing immune equilibrium and regulation. Given the deep-rooted understanding of Yin-Yang theory among Chinese students, we advocate for an educational strategy that contextualizes the concept of immune equilibrium within the framework of Yin-Yang, thereby offering a more intuitive and engaging learning experience. This method not only capitalizes on the cultural significance of Yin-Yang, but also corresponds to its principles of equilibrium and harmony, thus mirroring the homeostatic essence of immune responses. This article critically assesses this technique's capacity to bolster immune comprehension amongst Chinese students, while also considering its limitations. Despite these limitations, the fusion of these seemingly divergent fields holds substantial promise for augmenting immunology education, promoting critical thinking, and advancing cross-cultural academic discourse. The amalgamation of age-old philosophical insights with modern scientific exploration prompts a reassessment of educational methodologies within immunology, underscoring a novel pedagogical approach that bridges traditional wisdom with contemporary scientific education.